INOVASI DALAM MANAJEMEN KURIKULUM: PEMANFATAN TEKNOLOGI DALAM MENINGKATKAN PEMBELAJARAN - Devi Salimodo; Taruna Christofer S.; Agus Lestari (STAI Sangatta Kutai Timur, 2023)
This research aims to analyze the concept of educational technology, the function of ICT in learning, technology-based learning models, and barriers to its implementation. The method used in this research is the library research method. The research results show that educational technology is the application of science to learning to achieve effectiveness and efficiency. Innovative learning using educational technology can help build student character, develop scientific thinking skills, and increase student literacy. Technology-based learning models for instant project-based learning (PjBL), flipped classrooms, and self-organized learning environments (SOLE). Obstacles to its implementation are physical and non-physical obstacles. It is hoped this research will be able to provide a clearer view regarding the use of technology in improving the quality of learning and can assist in decision-making and continuous improvement in the education system.